The Impact of Foreign Direct Investment on Comparative Advantages in Foreign Trade – The Case of the CEE Countries - Katarzyna TWAROWSKA; Małgorzata TWAROWSKA-RATAJCZAK (Communications of International Proceedings, 2020)
The aim of the paper is an assessment of the impact of foreign direct investments (FDI) on the achievement by the Central and Eastern European (CEE) countries the revealed comparative advantages in exports. The panel regression analysis with random effects are used, which allow to examine the relation between the FDI inflow to particular industries and the having the revealed comparative advantage (RCA) in these industries. The analysis covers the period 2005-2015. The analyzed CEE countries are: Poland, Hungary, the Czech Republic, Lithuania, Latvia, Estonia, Slovenia, Slovakia. The analysis indicates that in the CEE countries FDI inflow was a significant factor influencing the export competitiveness measured by the RCA index. Furthermore, in the CEE countries the inflow of FDI in the manufacturing sector was relatively high and with economic development the importance of FDI inflow to the service sector increased. The structure of FDI inflow to the service sector is dominated by financial services. In industries with high FDI inflows, the improvement in RCA rates is noticeable. A new value of the analysis is the study of both the inflow of FDI and the achievement of comparative advantages at the level of industries. In addition, a particularly innovative analysis is for the service sector, which receives a significant part of FDI.
Keywords: Foreign Direct Investment; Exports; Comparative Advantage; Central And Eastern Europe